Effects of Temporary Numerical Imbalances on Collective Exploratory Behavior of Young and Professional Football Players - Canton, Albert; Torrents, Carlota; Ric, Angel; Gonçalves, Bruno; Sampaio, Jaime; Hristovski, Robert (Frontiers in Psychology, 2019)
The aim of this study was to explore how the use of temporary numerical imbalances during SSGs affects teams' exploratory behaviours (i.e. variety and quantity of responses given in an ever-changing game context and its rate of change) in different age groups. Two different age groups (under-15 and under-23) of football players participated in the study. For each age group, three teams of five players played 6 small-sided games of 5 minutes’ duration in different conditions: i) numerical balance (GK+4 vs. 4+GK); ii) temporary numerical imbalance, which consisted of a numerical change of teammates and opponents every one minute. Latitude and longitude GPS coordinates were used to determine the positioning-derived variables. The dynamic overlap (i.e. variable that provides information on the average similarity of the game patterns that take place in increasingly larger time intervals) was used to provide information of the rate and breadth of exploratory behaviour. The results revealed that the long-term exploratory breadth increased for the under-23 age group. Non-clear effects were found for the short-term rate of exploration, but with an increasing trend. In the under-15 group, the exploratory behaviour was more likely to increase in the long term. The increase for the short-term rate of exploration was unclear, but it follows an increasing trend. These results suggest that the use of temporary numerical imbalances could offer coaches more dynamic training situations and different adaptive training environments similar to matches.